Design mind for data visualization : learn to use information and graphic design principles to produce engaging data stories your audience can't ignore - Storm, J. (6X9 Publishing House, LLC, 2022)
93% of human communication is visual. Keep reading to get in on the conversation and level up your data visual designs with psychology-focused methods that tap into the MIND of your audience. Good graphic design can feel like a magic trick. In business, a well-designed data visual can tell a story that brings enlightenment and confidence to an audience. It helps stakeholders make decisions quickly. It provides invaluable insights to businesses based on data. It inspires new data scientists or analysts to explore their creative side. A viewer feels safe. They know they can trust the data. This is the power of design. It is important to tell your data story, but you must also show it. Let Design Mind help you put together the building blocks of design fundamentals and create a structure and process for you to use going forward